HORMONE REPLACEMENT THERAPY AND PREVENTION OF THROMBOTIC COMPLICATIONS - A. V. Vorob'ev; U. V. Zimovina; I. Z. Kvikviniya (Акушерство, гинекология и репродукция)
Pathogenesis of thrombotic complication caused by hormone replacement therapy and influence of HRT on risk of venous and arterial thrombosis are reviewed. Questionable points of prophylaxis of thrombotic complication of hormone replacement therapy are discussed.